Methanation of carbon dioxide over ceria-praseodymia promoted Ni-alumina catalysts. Influence of metal loading, promoter composition and alumina modifier. (15th December 2018) - Lechkar, Ali; Barroso Bogeat, Adrián; Blanco, Ginesa; Pintado, José María; Soussi el Begrani, Mohamed
Graphical abstract: Highlights: Ceria-praseodymia promoted Ni-alumina catalysts for CO2 methanation are prepared. Influence of Ni loading, promoter composition and alumina modifier is analyzed. The Ni content has the more pronounced influence, followed by the alumina dopant. The effect of Ce/Pr molar ratio in the promoter seems to be almost negligible. Ni(10 wt%)/Ce0.8 Pr0.2 O2-δ /Al2 O3 -SiO2 shows the best catalytic performance. Abstract: Two series of ceria-praseodymia promoted Ni-alumina catalysts were prepared from two different commercial modified alumina supports (3.5 wt% SiO2 -Al2 O3 and 4.0 wt% La2 O3 -Al2 O3 ) by the incipient wetness impregnation method in two successive steps. The resulting materials were characterized in terms of their physico-chemical properties by means of N2 physical adsorption at −196 °C, powder X-ray diffraction (XRD) and temperature programmed reduction with H2 (H2 -TPR). Furthermore, the as-prepared catalysts were tested for the CO2 methanation reaction in a fixed-bed reactor at atmospheric pressure, gas hourly space velocity (GHSV) of 72, 000 cm 3 ·(h·gcat ) −1 and CO2 /H2 molar ratio of 1/4 over the temperature range from 25 up to 850 °C. The influence of the nominal Ni loading (3, 5 and 10 wt%), molar composition of the Ce/Pr mixed oxide promoter (80/20 and 60/40), and alumina modifier (silica and lanthana) on the catalytic performance was carefully analyzed. Among these three composition parameters, the alumina dopant and especially the Ni content appear to have by far a much more pronounced effect on both the CO2 conversion and CH4 selectivity as compared to the Ce/Pr mixed oxide composition. Specifically, from the catalytic tests the sample containing a 10 wt% Ni loading, a Ce/Pr mixed oxide promoter of 80/20 molar composition, and silica as modifier provides the highest catalytic activity in terms of CO2 conversion and CH4 selectivity. Such behaviour has been ascribed to a complex interplay between several factors, mainly the larger fraction of catalytically active β-type NiO species and the lesser concentration of strong basic sites on the catalyst surface, as well as the electron back donation effect from the surface Ni atoms to the adsorbed COx species, which favours the C–O bond cleavage (i.e., the rate-determining step of the methanation reaction). These findings are expected to be very helpful in order to rationally design synthetic strategies that allow developing highly active and low cost Ni-based catalysts for the CO2 methanation reaction.